Advances in Human Factors and Systems Interaction Proceedings of the AHFE 2017 International Conference on Human Factors and Systems Interaction, July 17−21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA - Nunes, Isabel L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book reports on cutting-edge research into innovative system interfaces, emphasizing both lifecycle development and human-technology interaction, especially in virtual, augmented and mixed-reality systems. It describes advanced methodologies and tools for evaluating and improving interface usability and discusses new models, as well as case studies and good practices. The book addresses the human, hardware, and software factors in the process of developing interfaces for optimizing total system performance, particularly innovative computing technologies for teams dealing with dynamic environments, while minimizing total ownership costs. It also highlights the forces currently shaping the nature of computing and systems, including the need for decreasing hardware costs; the importance of portability, which translates to the modern tendency toward hardware miniaturization and technologies for reducing power requirements; the necessity of a better assimilation of computation inthe environment; and social concerns regarding access to computers and systems for people with special needs. The book, which is based on the AHFE 2017 International Conference on Human Factors and System Interactions, held on July 17-21, 2017, in Los Angeles, California, USA, offers a timely survey and practice-oriented guide for systems interface users and developers alike. .
Operators working with transmission flexibility: Enhancing utility control rooms with dynamic line rating technique -- The use of context aware pervasive systems in the area of human factors and ergonomics -- Augmented system verification using automated testing -- Knowledge management in the development of an intelligent system to support emergency response -- Visual search techniques and performance in electronic map display -- A comparative analysis of human-mediated and system-mediated interruptions for multi-user, multitasking interactions -- Development of an automated pressure sensitive thermesthesiometer and its application in characterizing the thermal response of human tissue with respect to warm surfaces -- S-EMG of forearm muscles activity in conventional PC mouse use.
Keywords: Computational intelligence; User interfaces (Computer systems).; Human-computer interaction; Electronics; Computational Intelligence; User Interfaces and Human Computer Interaction; Electronics and Microelectronics, Instrumentation